Associations between ethnicity, social contact, and pneumococcal carriage three years post-PCV10 in Fiji. Issue 2 (10th January 2020) - Neal, Eleanor F.G.; Flasche, Stefan; Nguyen, Cattram D.; Ratu, F. Tupou; Dunne, Eileen M.; Koyamaibole, Lanieta; Reyburn, Rita; Rafai, Eric; Kama, Mike; Ortika, Belinda D.; Boelsen, Laura K.; Kado, Joseph; et al.
Highlights: Pneumococcal carriage rates and the frequency of physical contact differed by ethnicity. Contact with older children and toddlers was positively associated with vaccine-type carriage. Unvaccinated older children may become a vaccine-type carriage reservoir post-PCV10. Ethnic differences in social contact did not explain ethnic differences in carriage. Pneumococcal density was not associated with ethnicity, contact, or PCV10 status. Abstract: Background: Pneumococcal carriage is a prerequisite for pneumococcal disease. Little is known about whether social contact frequency and intensity are associated with pneumococcal carriage. In Fiji, indigenous iTaukei have higher prevalence of pneumococcal carriage compared with Fijians of Indian Descent (FID). We hypothesised that contact differences may contribute to ethnic differences in pneumococcal carriage prevalence and density. Methods: In 2015, young infants (5–8 weeks), toddlers (12–23 months), children (2–6 years), and caregivers from Suva and surrounding areas, participated in a cross-sectional survey (n = 2014), three years post pneumococcal conjugate vaccine introduction. Demographic and contact data, and nasopharyngeal swabs were collected. Pneumococci were detected, and quantified using quantitative real-time PCR, with molecular serotyping by microarray. Associations between ethnicity, contact, and pneumococcal carriage and density were estimated using multivariable generalised estimating equation regression models. Results: iTaukei participants had larger household sizes, higher pneumococcal carriage rates, more contacts, and more frequent contacts of longer duration, compared with FID. The odds of vaccine-type carriage increased by 28% (95% CI 8–53%) P < 0.01 in association with physical contact with 7–14 year old children. iTaukei ethnicity was associated with vaccine-type carriage (aOR) 1.73; 95% CI 1.06–2.82, P = 0.03) and non-vaccine type carriage (aOR 5.98; 95% CI 4.47–8.00, P < 0.01). Ethnicity and contact were not associated with pneumococcal density. Conclusions: iTaukei had greater frequency and intensity of contact compared with FID. Physical contact was associated with pneumococcal carriage. Observed differences in pneumococcal nasopharyngeal carriage prevalence between iTaukei and FID were not explained by differences in social contact patterns by ethnicity.